Association of cognitive impairment with magnetic resonance imaging findings and social activities in patients with multiple sclerosis. Issue 3 (17th July 2014) - Niino, Masaaki; Mifune, Nobuhiro; Kohriyama, Tatsuo; Mori, Masahiro; Ohashi, Takashi; Kawachi, Izumi; Shimizu, Yuko; Fukaura, Hikoaki; Nakashima, Ichiro; Kusunoki, Susumu; Miyamoto, Katsuichi; Yoshida, Kazuto; et al.
Abstract Objective The aim of the present study was to investigate the association of magnetic resonance imaging (MRI) findings and social activity with cognitive function in Japanese patients with multiple sclerosis (MS). Methods The Brief Repeatable Battery of Neuropsychological tests (BRB‐N) was carried out in 184 Japanese patients with MS, and 163 controls matched for age, sex and education. MRI findings of cerebral, brainstem, and cerebellar lesions and social activities of MS patients were further examined. Results MS patients with higher numbers of cerebral lesions on MRI had lower scores in most BRB‐N tests. BRB‐N scores in the majority of tests were significantly lower in patients with brainstem and cerebellar lesions. Data from an analysis of variance model in which only the main effects of cerebral, brainstem and cerebellar lesions were hypothesized showed an association of cerebral lesions with decreased scores in all BRB‐N tests, except symbol digit modalities test (SDMT) and paced auditory serial addition test (PASAT). In contrast, cerebellar lesions were associated with decreased SDMT and PASAT scores. Patients categorized as "unemployed because of MS" had lower BRB‐N scores than other social activity groups. Lower SDMT scores had an effect on the "unemployed because of MS" group, whereas the Expanded Disability Status Scale had a significantly greater negative impact on patients in this social category. Conclusions Higher numbers of brain lesions on MRI could have an impact on cognitive function in patients with MS, and impairment of information processing appears significantly associated with cerebellar lesions. Cognitive impairment affects the employment status of patients with MS.